Stress and brain functional changes in patients with Crohn's disease: A functional magnetic resonance imaging study. Issue 10 (30th May 2017) - Agostini, A.; Ballotta, D.; Righi, S.; Moretti, M.; Bertani, A.; Scarcelli, A.; Sartini, A.; Ercolani, M.; Nichelli, P.; Campieri, M.; Benuzzi, F.
Abstract: Background: In Crohn's disease (CD) patients, stress is believed to influence symptoms generation. Stress may act via central nervous system pathways to affect visceral sensitivity and motility thus exacerbating gastrointestinal symptoms. The neural substrate underpinning these mechanisms needs to be investigated in CD. We conducted an explorative functional magnetic resonance imaging (fMRI) study in order to investigate potential differences in the brain stress response in CD patients compared to controls. Methods: 17 CD patients and 17 healthy controls underwent a fMRI scan while performing a stressful task consisting in a Stroop color‐word interference task designed to induce mental stress in the fMRI environment. Key Results: Compared to controls, in CD patients the stress task elicited greater blood oxygen level dependent (BOLD) signals in the midcingulate cortex (MCC). Conclusions & Inferences: The MCC integrate "high" emotional processes with afferent sensory information ascending from the gut. In light of these integrative functions, the stress‐evoked MCC hyperactivity in CD patients might represent a plausible neural substrate for the association between stress and symptomatic disease. The MCC dysfunction might be involved in mechanisms of central disinhibition of nociceptive inputs leading to amplify the visceral sensitivity. Finally, the stress‐evoked MCC hyperactivity might affect the regulation of intestinal motility resulting in exacerbation of disease symptoms and the autonomic and neuroendocrine regulation of inflammation resulting in enhanced inflammatory activity. Abstract : In CD patients, stress is believed to influence symptoms generation although the neural substrate underpinning this mechanism is unclear. Compared to controls, in CD patients a stress task elicited increased neural activity in the midcingulate cortex (MCC). The stress‐evoked MCC hyperactivity in CD patients might represent a plausible neural substrate for the association between stress and symptomatic disease. This hyperactivity might affect the intestinal motility and be involved in the disinhibition of nociceptive inputs leading to amplify the visceral sensitivity.